Determination of lattice physics properties and uncertainties in a solid fuel molten salt cooled assembly using OpenMC. (September 2021) - Mantecón, Javier González; Novog, David R.
Abstract: The desire for reducing our carbon footprint is driving significant interest in advanced nuclear reactors to produce energy. One promising technology is the Fluoride Salt-Cooled High-Temperature Reactor (FHR) which provides both electricity and high temperatures for use in process heat applications. The reactor technology considered in this work is a Generation IV design that uses TRISO particles uniformly embedded in fuel stripes within the fuel plates and liquid salt as coolant. The fuel design and conditions are the same as those used in a recent OECD/NEA FHR Benchmark. This paper reports the multiplication factor, fission reaction rate, and neutron spectrum for different cases from that benchmark study. A unique contribution of this work is the assessment of nuclear data uncertainty impact on the Figures of Merit used in the FHR benchmark. The OpenMC Monte Carlo code and perturbed nuclear data files from the TENDL-2017 library were utilized in these analyses. This work is part of the ongoing international efforts to explore and identify the applicability of current methods and codes for FHR simulations and molten salt reactors in general. Highlights: Uncertainty analysis of advanced nuclear system by using OpenMC. The multiplication factor decreases when the number of TRISO layers is incremented. The uncertainties of the thermal and epithermal fluxes are less than 0.9% for all cases.